Mechanical properties of Raphanus sativus L. seeds (Revista Ciência Agronômica, 2018)
The objective of this study is to determine the effect of moisture content on rupture strength, maximum strength,and rupture deformation for fixed deformations, and determine the proportional deformation modulus of seeds of Raphanussativus subjected to compressive loading. Seeds with a moisture concentration of 0.31, 0.18, 0.12, 0.08, and 0.05 decimal (drybasis, d.b.) were maintained in the natural resting position and were subjected to uniaxial compressive loading between twoparallel plates at an application rate of 0.002 m s-1. The rupture strength necessary to deform the seeds was increased from15.03 to 27.08 as moisture levels decreased. Deformation was increased from 0.12-3 m to 0.15 × 10-3 m as moisture contentdecreased. The maximum rupture strength and proportional deformation modulus in fixed deformations were increased asmoisture concentration decreased.